THE ISSUE OF INTERRELATION OF LANGUAGE AND POLITICS - Najimov Amanliq Shamshetdinovich (Research Focus International Scientific Journal, 2025)
This article defines the role of political terms in linguistics. The issue of the relationship between language and politics in the political process of society has been discussed. The importance of correct use of linguistic units is shown in the implementation of policy.